Delivery systems of local anesthetics in bone surgery: are they efficient and safe?. Issue 11 (November 2018) - Dupleichs, Manon; Gao, Qiman; Badran, Zahi; Janvier, Pascal; Bouler, Jean-Michel; Gauthier, Olivier; Tamimi, Faleh; Verron, Elise
Highlights: Postoperative pain following bone surgery is a frequent concern. Management of postoperative pain includes administration of local anesthetics. Optimized local anesthetic delivery systems should prolong duration of analgesia. High levels of local anesthetics affect tissue regeneration. Abstract : Management of postoperative pain following bone surgery includes administration of local anesthetics (LAs). Smart delivery systems, including triggered systems, have been designed to provide a continuous release of LA in situ . However, these systems can provide a high level of LA locally. This review will examine the state-of-the-art regarding the LA delivery systems optimized for management of postoperative pain in bone surgery and will discuss the potential adverse effects of LAs on the overall pathways of bone healing, including the inflammation response phase, hemostasis phase, tissue repair phase and remodeling phase. There is a clinical need to document these effects and the potential impacts on the clinical outcome of the patient.